Serologic IL-18 increase with B-cell IL-18R loss characterizes selective IgA deficiency - Lemarquis, Andri L.; Sigurgrimsdottir, Hildur; Theodors, Fannar P.; Karnsund, Ida; Einarsdottir, Helga K.; Jorgensen, Gudmundur; Ekwall, Olov; Jonsdottir, Ingileif; Ludviksson, Bjorn R. (Frontiers in Immunology, 2026)
IntroductionSelective IgA deficiency (sIgAD) is the most common primary antibody deficiency in Western populations and is associated with increased risks of respiratory infections, atopy, and autoimmunity. However, the serologic and B-cell–intrinsic pathways underlying this immune dysregulation remain poorly defined. We sought to characterize a population-based adult sIgAD cohort clinically and immunologically and to identify soluble and transcriptional signatures that link cytokine milieu to B-cell dysfunction.MethodsWe studied 61 adults with sIgAD and 73 age- and sex-matched healthy controls from the Icelandic sIgAD cohort. Participants completed standardized questionnaires on infections, atopy, and autoimmune disease. Serum immunoglobulins and autoantibodies (ANA, ENA, RF, CCP) were quantified, and a 65-plex Luminex cytokine/chemokine panel was measured in a subset of sIgAD individuals without active inflammatory disease and healthy controls. Purified CD19⁺ B cells from adults with sIgAD and controls were profiled by bulk RNA-seq at baseline and after 48 h TLR9 stimulation with CpG ODN 2006. Unsupervised analyses, differential expression, and correlation networks integrated clinical, serologic, and transcriptional data.ResultsClinically, adults with sIgAD had an airway-predominant infectious burden (notably increased sinusitis and pneumonia), a skin-skewed atopic pattern (eczema and urticaria), and frequent ANA/ENA positivity despite normal IgG and IgM. Immunoglobulin measurements showed very low IgA, increased total IgG and IgG1, and selectively reduced IgG4. Serum profiling revealed a coherent five-analyte signature, IL-18, sCD40L, TSLP, CCL3, and TWEAK, elevated in sIgAD and associated with higher IgG, lower residual IgA, and ANA/ENA positivity. This pattern was not reproduced in CpG-stimulated B-cell supernatants, indicating a non–B-cell origin. RNA-seq of purified B cells demonstrated diagnosis-dependent transcriptional programs at baseline and after CpG, with prominently reduced expression of IL-18 receptor components in sIgAD B cells.DiscussionAdult sIgAD is characterized by a blood-measurable endotype in which a systemic IL-18–centered soluble signature coexists with reduced IL-18 receptor expression and altered signaling programs in B cells. This IL-18-IL-18R axis aligns with ANA/ENA-associated immune dysregulation and an IgG-skewed class-switch profile, nominating IL-18–related mediators and B-cell IL-18R expression as candidate biomarkers and mechanistic targets in a subset of adults with sIgAD.